2018
DOI: 10.1186/s13660-018-1945-y
|View full text |Cite
|
Sign up to set email alerts
|

Small operator ideals formed by s numbers on generalized Cesáro and Orlicz sequence spaces

Abstract: In this article, we establish sufficient conditions on the generalized Cesáro and Orlicz sequence spaces such that the class of all bounded linear operators between arbitrary Banach spaces with its sequence of s-numbers belonging to generates an operator ideal. The components of as a pre-quasi Banach operator ideal containing finite dimensional operators as a dense subset and its completeness are proved. Some inclusion relations between the operator ideals as well as the inclusion relations for their duals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 16 publications
1
63
0
2
Order By: Relevance
“…Finally, we show that the prequasi Banach operator ideal formed by the approximation numbers and is small under certain conditions. These results coincide with that known for , (1 < < ∞) in [3]. Furthermore we give some examples which support our main results.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…Finally, we show that the prequasi Banach operator ideal formed by the approximation numbers and is small under certain conditions. These results coincide with that known for , (1 < < ∞) in [3]. Furthermore we give some examples which support our main results.…”
Section: Introductionsupporting
confidence: 92%
“…(1) for all ∈ Ω( , ), ( ) ≥ 0 and ( ) = 0 if and only if = 0, Theorem 29 (see [3]). Every quasi norm on the ideal Ω is a pre-quasi norm on the ideal Ω.…”
Section: Definition 28 (See [3]) a Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bakery and Mohammed investigated the operator ideals generated by s-numbers and Orlicz-Cesáro mean sequence spaces. In [34], Faried and Bakery introduced the concept of pre-quasi operator ideal which is more general than the quasi operator ideal, studied the operator ideals formed by s-numbers, generalized Cesáro and Orlicz sequence spaces ℓ M and showed that the operator ideal formed by approximation numbers and the previous sequence spaces is small under certain conditions. Many articles have been published on the above topics, sequence spaces defined by Orlicz function, multiplier sequences, spectra of matrix operators etc in the recent past by Tripathy et al [35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Makarov and Faried (see [20]) proved that, for any infinite dimensional Banach spaces X, Y and for any q > p > 0, S app p (X, Y ) is strictly contained in S app q (X, Y ). Faried and Bakery (see [21]) introduced the concept of pre-quasi-operator ideal which is more general than the usual classes of operator ideal, they studied the operator ideals formed by s-numbers, generalized Cesáro and Orlicz sequence spaces M , and showed that the operator ideal formed by approximation numbers and the previous sequence spaces is small under certain conditions. The aim of this article to study the concept of pre-quasi-norm on C(p) which is more general than the usual norm, and give the conditions on C(p) equipped with the prequasi-norm to be Banach space.…”
Section: Introductionmentioning
confidence: 99%